PROMOTING STUDENT HEALTH THROUGH THE GAME OF BASKETBALL - Ravshanzhon Solijonovich Mamatkulov (Galaxy International Interdisciplinary Research Journal, 2023)
The level of health of students of non-physical education universities was studied. It is shown that the modernization of the system of physical education has led to a significant reduction in classroom physical education. The connection between the low level of health of students and the reduction of classroom physical education classes is considered.